Analysis of the main indicators regarding the production and surface area of the main crops in the South-East development region, in the period 2010-2018 - Gabriela-Dalila Stoica (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
Cereals are grown for grain and are used both to provide food and feed. In Romania, cereals occupy an important place in the structure of use of agricultural areas, observing a tendency to increase the areas where cereals are grown due to their importance, but also due to the fact that Romania has favorable soil and climatic conditions for their growth and development. The research aims to analyze the evolution regarding the areas, total productions and average productions obtained within the South-East region, in the period 2010-2018.
Keywords: Q10; R14; 330; crop production; cultivated area; South-East region